Psychoeducation Program for Substance Use Disorder Effect on Relapse Rate, Social Functioning, Perceived Wellness, and Coping - Kargin, Maral; Hicdurmaz, Duygu (Slack Inc, 2020)
The current study was designed to assess the effect of a psychoeducation program on relapse rate, social functioning, perceived wellness, and ways of coping in individuals with substance use disorder (SUD).The study sample comprised 92 individuals (n = 46 intervention group, n = 46 control group) who received SUD treatment, had undergone detoxification, and agreed to participate in the study. A 10-session psychoeducation program was applied to individuals in the intervention group. Data collection included a urine sample and completion of the Personal Information Form, Social Functioning Scale, Perceived Wellness Scale, and Ways of Coping Scale. The relapse rate in the control group was found to be higher than in the intervention group; thus, it was determined that the relapse prevention psychoeducation program led to positive changes in relapse rate, social functioning, perceived wellness, and stress in individuals with SUD.
Keywords: Prevention; Individuals; Therapy; Intervention; Symptoms; Seeking; Styles; People